The Wakayama earthquake swarm in Japan - Junichi Nakajima (Earth, Planets and Space, 2023)
Abstract An earthquake swarm in the Wakayama prefecture, Japan, is known as the most active and persistent swarm, with > 95,000 earthquakes (M ≥ –1.3) occurring during the 2003–2020 period. However, no systematic studies have highlighted the source of this intriguing non-volcanic earthquake swarm to date. This study systematically investigates the temporal and spatial evolution of the Wakayama earthquake swarm and estimates the seismic velocity structure around the Kii peninsula, where we observe series of anomalous geophysical and geochemical signatures, such as high 3He/4He ratios, deep low-frequency earthquakes, and hot springs with high salinity and solute concentrations. We reveal that seismicity associated with the Wakayama earthquake swarm occurs almost evenly in both time and space, and that the majority of the earthquakes in the northern part of the swarm activity occur along well-defined planes that dip to the west at 30–45°. The seismic tomography results reveal that a northwestward-dipping low-velocity zone exists beneath the Wakayama swarm and the low-velocity zone is sandwiched by high-velocity anomalies in the continental crust interpreted as impermeable and rigid materials on both sides in the subduction direction. This unique tectonic setting controls a pathway of the upward migration of slab-derived fluids to the surface, with the high fluid concentration in the dipping low-velocity zone. Therefore, we infer that the location of the Wakayama swarm is controlled by deep crustal heterogeneities rather than by the major structures of geological accretionary complexes. This study suggests that the anomalous geophysical and geochemical signatures observed across the Kii peninsula are different manifestations of the frictional and hydrological processes during the upward migration of the slab-derived fluids. We further propose that the valley-shaped geometry of the Philippine Sea slab beneath the Kii peninsula is caused by the rigid materials in the continental crust. Graphical Abstract